(untitled) (Pedagogy of Higher and Secondary Education, 2013)
Davydenko H. V. The Implementation Of Inclusive Education In Great Britain: Obstacles, Future Challenges. The results of analysis of basic problems of inclusive education in Great Britain are presented in the article. Obstacles are examined at the level of governmental activity, local authorities and local communities. The special attention is paid to the analysis to the state of businesses in the system of school education and searches of measures for overcoming of the obstacles in access to education.